« Récit concentrationnaire » et « prose d’idées » - Lucie Bertrand (Cahiers de Narratologie)
The french word used to group together nazi’s camps survivor’s writings is detrimental to some of them which hinge on the same fundamental features. As a matter of fact, the appellative “récit concentrationnaire” gathers all those writings on the basis of their testimonial and historical dimension. As a consequence, writings which share those features but possess crucial didactic goals and a deep reflection on how to tell the unspeakable are not acknowledged for their specificities. Relying on Robert Antelme’s Espèce humaine as an example of this kind of writings, we aim at questioning the traditional classification. We consider the “prose d’idées” as a good mean to gain our aim: may be this expression could fit the writings we deal with. And may be, in return, asking this question can lead us to approach this latter from a new angle.